Evaluasi Kebijakan Kawasan Tanpa Rokok Kota Semarang (peraturan daerah kota Semarang nomor 3 tahun 2013 tentang kawasan tanpa rokok). - M Septian Budiman; Suwanto Adhi; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2018)
Semarang city as one of the autonomous regions, has actually implemented the legal obligation by entering the non-smoking area through Semarang city are of regulation no 3 of 2013 about area without smoking. The government is attempling to reduse and limit the society who smoke in order to reduce diseases caused smoking, the smoker from theactive and passive smokers. The research aims to determine whether regulatorypolice areas no 3 of 2013 is already or implemented property.The method used in this study using descriptive the subject of this research is the government that represented by the health office of Semarang city and Salpol PP Semarang city, responsible for the implementation of the policy and the community.Based on the result of research wich can concluded: Implementation of the local regulation no 3 of 2013 about non smoking area in Semarang city has not run in accordance with is expected. Its still violations disciver and a less good response from the public. Keywords: Implementation, regulation, non-smoking area